PENGGUNAAN DAUN PISANG (MUSA PARADISIACA) SEBAGAI MEDIA PADA BUDIDAYA JAMUR COPRINUS COMATUS - Ali Akbar; Elisa Herawati (Politeknik Pertanian Negeri Samarinda, 2017)
This research is motivated because other uses of sawdust in Indonesia are only a few areas, therefore we need another alternative media that can be used to replace the media for sawdust, namely banana leaves. Therefore, this study aims to determine the speed of mycelium growth, the time it takes when the pinhead emerges, the time it takes at harvest 1 and 2, the number of fruit bodies at harvests 1 and 2, the average hood width at harvest 1 and 2, weight of mushrooms. Coprinus comatus at harvest 1 and 2 and the mean BERny value using banana leaves. The method used was to make 15 baglog samples with the planting medium of 100% banana leaves with a total sample weight of 4,500 grams.The important research results are the average period of mycelium growth is 42 Hsi and the emergence of pinhead 1 (small mushroom shoots) is 43 Hsi, then the harvest period 1 is 44 Hsi, the emergence period of pinhed 2 is 48 Hsi and harvest 2 is 49 Hsi. The total weight of harvest 1 was 39.88 grams with the number of fruit bodies 43 and the average number of hood widths was 19.85 cm. The total weight of the harvest 2 was 27.25 grams with the number of fruit bodies 19 and the average width of the hoods was 8.25 cm. The total harvests 1 and 2 were 67.13 grams of the total baglog weight of 4,500 grams. The average BER value of Coprinus comatus for banana leaf media was 1.49%. Overall, the growth rate of mycelium, pinhead and fruiting bodies is relatively slow. It is suspected that the cause of the sufficient time required for the growth of mycelium and the emergence of pinheads and the formation of fruit bodies is the longer fermented banana leaf media or the temperature and humidity conditions in the kumbung that do not meet the optimal conditions for Coprinus comatus mushroom growth or a combination of both.